(untitled) (Historia, 2025)
Zimbabwe People’s Revolutionary Army (ZPRA) guerrilla warfare from the early 1960s to 1979 was fought by armed men at the front,while trained female cadres remained in the rear bases. Recruitment, training, deployment and battlefield experiences ran alongside orientation in the African home which was inclined towards male aggression and female submissiveness. Complex masculinities in this guerilla army remain a grey area of study and influence how the former fighters look meanly at one another today. Data for this article was drawn from autobiographies and interviews with former ZPRA combatants, Zimbabwe African People’s Union (ZAPU) publications and secondary sources, to interrogate the link between masculinity and militarism. This research established that ZPRA guerilla warfare was a meeting-point of complex masculinities with each individual guerilla discharging military duties in accordance with circumstances of the time. The article contributes to the understanding of how men behave in a war situation. The suffering and feminisation of men has not attracted much academic attention in accounts of guerilla fighters, who since the attainment of independence in 1980, became either heroes or villains. The research on masculinity contributes to men’s perceptions of their role in armed conflict.